2017
DOI: 10.1039/c7nr03895j
|View full text |Cite
|
Sign up to set email alerts
|

Dry spinning approach to continuous graphene fibers with high toughness

Abstract: Graphene fiber (GF) has emerged as a new carbonaceous fiber species since graphene-based liquid crystals were discovered. The growing performances of GFs in terms of their mechanical performance and their functionalities have assured their extensive applications in structural materials and functional textiles. To date, many spinning strategies utilizing coagulation baths have been applied in GF, which necessitates a complicated washing process. Dry spinning is a more convenient and green method for use with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…GO fibers can be reduced to graphene fibers by HI. The mechanical strength and toughness of the graphene fibers were 375 MPa and 19.12 MJ m −3 , respectively . Typically, the prepared fibers by dry spinning method usually exhibit better mechanical properties than those by wet spinning.…”
Section: Preparation Of 2d Crystal–based Fibersmentioning
confidence: 99%
“…GO fibers can be reduced to graphene fibers by HI. The mechanical strength and toughness of the graphene fibers were 375 MPa and 19.12 MJ m −3 , respectively . Typically, the prepared fibers by dry spinning method usually exhibit better mechanical properties than those by wet spinning.…”
Section: Preparation Of 2d Crystal–based Fibersmentioning
confidence: 99%
“…Unfortunately, for the best of our knowledges, the studies of the dry spinning GFs are still very limited. When this paper is still under review, Gao’s group firstly reported dry spinning GFs 25 . Even though extruding high concentrated GO gel has been announced by other groups in their investigation of 3D printing graphene structures 26 , 27 , the rheological properties of GO, as well as its physical impact on the drying dynamics, micro-structures and mechanical properties of the prepared fibers still need to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of the fiber can be affected controlling take up speed, length to diameter ratio of the spinneret, environment or temperature, and spinning rate [ 126 , 145 ]. Additionally, subjecting the dry-spun fiber to a post-treatment agent or post-formation drawing can enhance mechanical properties [ 126 ].…”
Section: Fabrication Methodsmentioning
confidence: 99%